Posted by **Jon** on Saturday, March 1, 2008 at 9:48am.

Assume that no denominator equals 0.

2+i/1-3i

= 2+i/1-3i

= (2+i/1-3i) * (1+3i/1+3i)

= (2+3i^2)/(1-9i^2)

= (2/1) - (1/3i)

= 2-1/3i(answer)

## Answer this Question

## Related Questions

- Algebra II (check) - Assume that no denominator equals 0. (2x-3)^2 = 2x * 2x -3...
- Algebra II (check) - Assume that no denominator equals 0. 5x^3(7x)^2 = 5*7*7+x^3...
- Algebra II (check) - Assume that no denominator equals 0. sqrt 16x^2y^4 = sqrt (...
- Algebra II (check) - Assume that no denominator equals 0. (8y^3+27)/(2xy-10y+3x-...
- Troy - Can someone check my answers for the following problems. Simplify. Assume...
- Algebra II (check) - Assume that no denominator equals 0. sqrt12 - sqrt18 + ...
- Algebra - Divide. Show all work. Make sure to simplify. Assume no denominator ...
- algebra - Solve for x x/6-x/8 equals 1 Do fraction busters Find the least common...
- algerbra 2 - B. The rational expression is not defined for any values of 20^2-...
- algebra - simplify. assume no denominator is eual to zero. -10m-1y0r(numerator...